نشأة الفرق الإسلامية بين حتمية التفرّق وضرورة التعايش: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Abbas dhahri, Dr. (lark, 2022)
The issue of the emergence of Islamic sects and sects in the history of Islam for some was considered a reason for the decline of the Islamic nation and its difference, so this research paper seeks to respond to this claim on the grounds that religious texts emphasize the inevitability of separation and consider it a civilizational and intellectual necessity, which throughout history contributed to creating cultural diversity and sectarian pluralism According to the different mental perceptions and intellectual premises, what drives the necessity of coexistence and acceptance of the difference of the other.